Effect of Repetitive voltage Sag on Contactor Behavior - Hardi, Surya; J Sinaga, Desman; ., Rohana (International Journal of Engineering and Technology, 2018)
Contactor is one of device used in many industries which it is as connector between electric motor and source voltage. It is identified as susceptible device against voltage sag. In distribution system, repetitive voltage sag occurred due to operate automatically of re-closer to open and reclosing when fault. This study is to investigate effect of repetitive voltage sags on contactor behavior under distinct POW. Difference of voltage sag duration in first sag was applied to second sag in various POW of 0o, 45o, and 90o. Time difference between first and second sags occurrence is 500ms and fixed, it is according to time delay range of operation re-closer. Time required of contactorâ€™s contact to open under distinct the POW are observed. The contactor is faster to drop out in the second sag compared with first sag when it was applied by repetitive voltage sag with 0o POW. Otherwise the contactor to drop out in the second sag is longer than first sag when it was applied repetitive voltage sag under 90o POW of sag initiation. Effect of voltage sag with 45o POW causes the contactor to release it contact in similar duration time.Â Â